Efektivitas air rebusan bawang dayak (Eleutherine palmifolia (L.) Merr) dalam menghambat pertumbuhan bakteri Escherichia coli pada daging sapi - Mey Angraeni Tamal; Dhani Aryanto (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2020)
At this time many food processing used chemical preservatives that can interfered human health. Dayak onion plants was widely used as medicine because they contain antimicrobial substances. Efforts to increase the used of natural preservatives from plants so that plants would be able to replace chemical preservatives. However, this plant had not been used as a natural preservative so there was a need for research to increase knowledge of other benefits, especially as preservatives for stored livestock products. The purpose of this study is to determine the best concentration of boiled water of dayak onion (Eleutherine palmifolia (l.) Merr) to inhibiting the growth of escherichia coli bacteria and how long the meat has been stored is still in good condition at room temperature and how much was the best concentration of boiled water of Dayak onions. The method used was descriptive analysis. The stages of the study were the manufactured of boiled water of dayak onion 0, 10, 20 and 30% w/v, soaked for 15 minutes, packed, storaged at room temperature 22-32 OC and E. coli tested at the Animal Health and Veterinary Public Health Laboratory of Samarinda. The results of the study were boiled water of dayak onion had an effect as an antimicrobial agent at a concentration of 30% w/v, there was a tendency to reduced the number of E. coli bacterial colonies in beef and the best storaged treatment was 1 day.